Karakteristik Permukiman Kumuh di Kawasan Pesisir Kota Bandar Lampung - Rahmah, Chania; Pakpahan, Zahrotunnur Rumondang; Syawaludin, Ilham Candra; Sihombing, Elkana Maruli; Anandirza, Farah Alfia; Melinda, Dara; Simbolon, Ruth Mentari; Batya, Ghyseila (Jurnal Perencanaan dan Pengembangan Kebijakan, 2025)
Urban growth often leads to various issues, one of which is slum problems. This study identifies the characteristics of slum settlements in the coastal area of Bandar Lampung City, with the aim of understanding the physical and non-physical conditions that influence slum development. The slum settlements in the coastal area emerged due to geographic, social, economic factors, and non-compliance with regulations, making them vulnerable to natural disasters. The method used is qualitative descriptive, with data collection through observation and questionnaires. The results indicate that the slum settlements are divided into two types: those located on land and those standing above the sea. The infrastructure conditions in these slum areas are very poor, including irregular building structures, non-compliance with technical standards, and deficiencies in waste water management, garbage collection, and fire protection. The socio-economic aspects of the community also show low levels of welfare, with the majority of the population working in the informal sector. This research is expected to contribute to the formulation of strategies for addressing slum settlements in the coastal area of Bandar Lampung.